Perbedaan Pengaruh Teknik Relaksasi Nafas Dalam Dan Kompres Hangat Dalam Menurunkan Dismenore Pada Remaja SMA Negeri 3 Padang: The Difference in the Effect of Deep Breathing Relaxation Techniques and Warm Compresses in Reducing Dysmenorrhea in Adolescents at SMA Negeri 3 Padang - Vetty Priscilla; Dwi Christina Rahayu Ningrum; Lili Fajria (Fakultas Keperawatan Universitas Andalas, 2012)
Some women experience dysmenorrhoea in each menstrual cycle, the intensity of pain that is felt even to severe and interfere with the activity. One non-pharmacological therapies that can be done to reduce dysmenorrhea relaxation techniques and breathing in the warm compresses. The purpose of this study to determine the influence of different relaxation techniques and breathing in the warm compresses in reducing dysmenorrhea in adolescent girls in SMA Negeri 3 Padang. This study uses a quasi experiment design. Sample as many as 32 teens divided in each treatment with the execution time of 20 minutes. Statistical tests used were t-test test and test of paired samples t-test free samples. The results showed there were significant reductions in the scale of dysmenorrhea in each group (p = 0.000). Bivariate analysis showed no significant difference scale reduction of dysmenorrhea in adolescents who were given relaxation techniques and breathing in the warm compresses. Based on this study suggested the teens use deep breathing relaxation techniques and warm compresses as one alternative to decrease pain of dysmenorrhea.